Membangun Sistem Informasi Pembiayaan PT Rafflesia Finance Dengan Metode Sekuensial Linear - Tedy Enggriano; Kirman; Diana (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
PT Rafflesia Finance is engaged in motorcycle financing, particularly financing for Honda motorcycles. In line with the business transformation carried out, the company continues to develop and not only provides financing for Honda motorcycles, but also financing for other Japanese motorcycle brands, such as Yamaha, Suzuki and Kawasaki. One of the five missions of PT Rafflesia Finance is to build IT-based infrastructure to implement good processes in order to optimize company performance. To realize this mission, a system is needed that can help the company's business processes. So that the application that is formed is truly in accordance with the needs, the system development uses a linear sequential method and an application test is carried out using the black box testing method.